'Now that you mention it, museums probably are a target': museums, terrorism and security in the United Kingdom. (3rd March 2020) - Atkinson, Colin; Yates, Donna; Brooke, Nick
ABSTRACT: This article explores counter-terrorism security practices at museums in the United Kingdom (UK), locations that terrorists have targeted through both propaganda and operational activity. Drawing upon research that re-interprets the museum within the 'single narrative' of global jihadist terrorism, an outlook that justifies and legitimises the targeting of socio-cultural sites from instrumental and symbolic perspectives, this article highlights the important roles of the police Counter Terrorism Security Adviser (CTSA) and the museum security manager in counter-terrorism practice at museums in the UK. The practices of highlighting risk to the museum and managing risk in the museum environment are subsequently outlined. In doing so two key challenges facing counter-terrorism security practice in the museum are noted: the cost of implementing counter-terrorism measures and the cultural challenge of communicating and responsibly embedding such security thinking in everyday practice. The researchers also reflect upon the potential consequences of the implementation of counter-terrorism security measures at museums as a form of securitisation.